LITERASI MEDIA SOSIAL SEBAGAI UPAYA PENANGGULANGAN HOAX INFORMASI KESEHATAN PADA MASYARAKAT PESISIR DI DESA NII TANASA KECAMATAN LALONGGASUMEETO KABUPATEN KONAWE - Muhammad Ikhsan Akbar (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The rapid development of information and communication technology in this digital era has affected the pattern of human life. According to digital data uploaded by Hootsuite and released in January 2020, the number of active social media users in Indonesia increased by 8.1 percent compared to the previous year. The total touched 160 million users. The purpose of the service activity is to provide health education as an effort to tackle hoax news to coastal communities in Nii Tanasa Village based on social media literacy. This service uses the lecture method to 27 communities in Nii Tanasa Village, Lalonggasumeeto District. Health education participants were very enthusiastic about participating in counseling with a questionnaire giving session to measure the level of public knowledge. The results obtained were that the level of community knowledge was low before counseling was carried out with a poor value of 74% and a good value of 26%, then after counseling there was an increase in knowledge with a poor value of 14.8% and a good value of 85.2%, it can be concluded that from this service program there was a significant increase in knowledge.